Series Compensation of Transmission Systems: A Literature Survey - Camilo Andrés Ordóñez; Antonio Gómez-Expósito; José María Maza-Ortega (Energies, 2021)
This paper reviews the basics of series compensation in transmission systems through a literature survey. The benefits that this technology brings to enhance the steady state and dynamic operation of power systems are analyzed. The review outlines the evolution of the series compensation technologies, from mechanically operated switches to line- and self-commutated power electronic devices, covering control issues, different applications, practical realizations, and case studies. Finally, the paper closes with the major challenges that this technology will face in the near future to achieve a fully decarbonized power system.